DMAIC Approach for Road Wellbeing: A Case Study - Ravi Shankar Raman, Mr.; Himanshu Chauhan, Mr.; Ankit Negi, Mr. (International Journal of Engineering and Technology, 2018)
The objective of this paper is to implement the DMAIC methodology for finding out the reason for the traffic jam in the NH-24 connecting Delhi, Ghaziabad and Noida and finding out the solution for reducing them. For this survey, we have collected the data of a fixed route for 14 days and implemented various statistical methods for analyzing it. The study, focused on various junctions because these are the points, which are more prone to congestion. It aimed at finding out the critical junction and suggest improvement in them.Â As the number of vehicles is on the rise, it is the need of the hour to solve this problemÂ Â